2014
DOI: 10.1177/1468087414545094
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature of selective catalytic reduction catalysts integrated into diesel particulate filters

Abstract: Combining the functions of selective catalytic reduction with the diesel particulate filter provides the opportunity in light- to heavy-duty applications for design and packaging flexibility, improved thermal management and reduction of the aftertreatment system volume, mass and cost. This integration can be achieved by washcoating the selective catalytic reduction catalyst on and/or in the diesel particulate filter substrate wall. With packaging flexibility and closer placement of the selective catalytic redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…The motivation for the integration of the two reactions is to obtain a reduction of cost and volume of the engine after-treatment system via inclusion of SCR and DPF functionalities into a single entity. Different bi-functional configurations are possible with DPF and SCR catalyst placed in the same housing [7], or with a DPF filter coated with an SCR catalyst formulation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for the integration of the two reactions is to obtain a reduction of cost and volume of the engine after-treatment system via inclusion of SCR and DPF functionalities into a single entity. Different bi-functional configurations are possible with DPF and SCR catalyst placed in the same housing [7], or with a DPF filter coated with an SCR catalyst formulation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The location of PM was found to have minimal e↵ect on PM oxidation rate. Also, for the CSF, it was found that PM oxidation rate increased with increase in Pt catalyst loading with 40 g/ft 3 filter having higher PM oxidation rate than 10 g/ft 3 . Pt was found to not catalyze the NO 2 based PM oxidation but instead caused an increase in the NO 2 available in the PM cake by oxidizing NO to NO 2 unlike the catalyst Cu-Ze in the SCRF® which did not oxidize a significant amount of NO to NO 2 .…”
Section: Scr-f Modelsmentioning
confidence: 91%
“…Xiaobo Song et al [3] conducted a literature review of papers involved with a SCR catalyst on DPF's related to catalyst design, performance characterization and modeling which was carried out as part of the MTU Diesel Engine Aftertreatment Consortium. The main conclusions from this paper are :…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations